Business 2000 - Greene, Cynthia
Enter the world of creative selling! Business 2000: Selling shows you how to determine your clients needs and wants, prepare to sell, develop the sale, and close the sale! Developing skills for successful selling and incorporating technology into the sales process are also important features of this text